ABCG1 Attenuates Oxidative Stress Induced by H2O2 through the Inhibition of NADPH Oxidase and the Upregulation of Nrf2-Mediated Antioxidant Defense in Endothelial Cells - Jiahong Xue; Jiali Fan; Yuan Li; Wenhuan Wu; Qing Yan; Qiangsun Zheng (Analytical Cellular Pathology)
Summary. Oxidative stress is an important factor that is related to endothelial dysfunction. ATP-binding cassette transporter G1 (ABCG1), a regulator of intracellular cholesterol efflux, has been found to prevent endothelial activation in vessel walls. To explore the role of ABCG1 in oxidative stress production in endothelial cells, HUAECs were exposed to H2O2 and transfected with the specific ABCG1 siRNA or ABCG1 overexpression plasmid. The results showed that overexpression of ABCG1 by ABCG1 plasmid or liver X receptor (LXR) agonist T0901317 treatment inhibited ROS production and MDA content induced by H2O2 in HUAECs. Furthermore, ABCG1 upregulation blunted the activity of prooxidant NADPH oxidase and the expression of Nox4, one of the NADPH oxidase subunits. Moreover, the increased migration of Nrf2 from the cytoplasm to the nucleus and antioxidant HO-1 expression were detected in HUAECs with upregulation of ABCG1. Conversely, ABCG1 downregulation by ABCG1 siRNA increased NADPH oxidase activity and Nox4 expression and abrogated the increase at Nrf2 nuclear protein levels. In addition, intracellular cholesterol load interfered with the balance between NADPH oxidase activity and HO-1 expression. It was suggested that ABCG1 attenuated oxidative stress induced by H2O2 in endothelial cells, which might be involved in the balance between decreased NADPH oxidase activity and increased Nrf2/OH-1 antioxidant defense signaling via its regulation for intracellular cholesterol accumulation.